Identification of patients with primary ovarian insufficiency caused by autoimmunity. Issue 4 (October 2017) - Gao, Jing; Jiao, Xue; Dang, Yujie; Li, Jing; Li, Guiyu; Han, Ting; Liu, Yixun; Qin, Yingying; Chen, Zi-Jiang
Abstract: Autoimmune pathogenesis is responsible for a subset of primary ovarian insufficiency (POI) cases. The significance of autoantibodies for POI, however, remains unclear. A total of 250 women with idiopathic POI and 256 age-matched healthy women were enrolled. The presence in serum of adrenal cortex autoantibody (AAA), detected by indirect immunofluorescence and non-organ-specific antibodies, including antinuclear antibody, anti-cardiolipin antibody, and anti-double stranded DNA antibody, detected by enzyme-linked immunosorbent assay, was compared. Ovarian biopsy was carried out for histology assessment. Adrenal function was followed-up in 15 women with POI who were positive for AAA. Higher frequency of positive AAA was observed in women with POI (19.2%) compared with controls (5.9%, P < 0.01). No difference in anti-cardiolipin antibody, antinuclear antibody and anti-double stranded DNA antibody was found between the two groups. Ovarian biopsies in 13 women with POI (six AAA positive and seven negative) showed atrophic ovaries devoid of follicles. One out of fifteen women positive for AAA had symptoms of adrenal insufficiency 3 years after POI diagnosis. Significantly higher positive frequency of AAA in POI patients suggests the role of autoimmune disturbance in pathogenesis. Therefore, AAA may serve as a biomarker for ovarian autoimmunity.